PROFILING AND GROUPING OF FLAVONOID COUMPOUND USING LCMS FROM A COMBINATION OF WHITE TURMERIC EXTRACT AND HONEY AND ITS BIOACTIVITY TEST IN OBESE RATS - BOGORIANI, NI WAYAN; EKA PRATIWI, I GUSTI AYU PUTU; SUANITI, NI MADE; DEWI, KOMANG TRIA NOVIANA (International Journal of Applied Pharmaceutics, 2026)
Objective: The aim of this study was to identify and classify flavonoid compounds from a combination of white turmeric (Curcuma zedoaria) extract and honey, which have the potential as anti-obesity and anti-diabetic type 2 agents in obese Wistar rats. Methods: This study used 25 rats divided into 5 groups, namely the normal, the obese, the obese group plus 100 mg/kg bw white turmeric extract, the obese group plus 100 mg/kg bw honey, and the obese group plus the combination of white turmeric and honey. The treatment was carried out for 4 w and the parameters measured were body weight, free fatty acid, glucose, and serum triglycerides levels of rats. Identification of flavonoid compounds using Liquid Chromatography-Mass Spectrometry (LC-MS). Results: The results showed that the combination of white turmeric extract and honey was able to reduce the weight of rats (Lee's obesity index), free fatty acid (FFA), glucose and triglycerides (TG) levels with significant differences (p<0.05) from the obese rats. The average decrease in glucose, triglyceride, free fatty acid, and Lee's obesity index levels was 66.12%, 74.31%, 42.57%, and 20.59%, respectively. The results of LC-MS analysis identified 33 flavonoid compounds from white turmeric and 15 flavonoids from honey, which are thought to play an active role in reducing weight, free fatty acids, glucose and triglycerides. Conclusion: The results of this study stated that there were 48 flavonoid compounds identified from the combination of white turmeric extract (Curcuma zedoaria) and honey which have the potential as anti-obesity and anti-diabetic type 2 in obese wistar rats.